FITNESS FOR EACH SCHOOL SEX IN BASIC EDUCATION SERIES STARTED IN PHYSICAL EDUCATION ACTIVITY PIBID / IFPR (Fiep Bulletin - online, 2014)
Introduction: The scientific literature shows the development impact of physical fitness on health. Objective: To assess the level of physical fitness in relation to sex in school is a public institution of elementary education - early grades. Methodology: A descriptive cross-sectional quantitative study. 31 students were studied, 19 males and 12 females, aged between 7 and 11 years, physical fitness tests proposed by PROESP being applied: 1 - Testing power of lower limbs; 2 - Test flexibility; 3 - Test speeds (20m race). Data were analyzed using descriptive statistics of mean and dispersion and is attested by the significance test (p
Keywords: Physical fitness; Speed; Strength; Flexibility.